A crítica marxiana à política no período de 1843-1848 - Carla Valeria de Avila Gallego (2002)
The present work treatsthe Marxian political critique from 1843 to 1848. Starting from the fundamental outcome of the Critique of Hegel's Philosophy of Right present that the thesis from "Deusche-Französische Jahrbücher" and the "Vorwarts" are developments which deeply analysis the question of Determination of civil society on the State, thereby the political actions are ineflective for solving the social problems. After theidentification of the determined character of society over the political sphere, we analysed the material relations from the features, which run the modern way of production. Firstly, private property appears as responsible for reproducing the social alienation and the State arises asillusory representative of human sociability, which does not occur by the eíTective social relations. Secondly, by the analysis of civil society, the division of labour appears as determined of modern social structure that portrays the conflict and the domination of class. Therefore, the Stale emerges as an abstract sphere, representing the general interest of thedominant class. Conclusively, we may say that the State and th^ politics are spheres that alienate the human social forces, that is, those are spheres originated and kept by intrinsic problems of the own social formation.